Stock Price Assessment with Fundamental Analysis as a Basis for Investment Decision Making - Asyifa Melati Sukma Ratu Nyaman; Munasiron Miftah (Budapest International Research and Critics University, 2022)
Fluctuating stock prices in the capital market cause investors to conduct an analysis first before making a decision whether to buy or sell shares. By conducting technical and fundamental analysis, investors can make investment decisions. Fundamental analysis can be done with several methods of stock valuation, which in this study uses the PER, DDM, DCF funds to see the intrinsic value of the stock. The study was conducted by comparing the intrinsic value with market value, thus indicating whether the stock is overvalued or undervalued. When the stock is in an overvalued condition, investors can sell, and vice versa. Because there are differences in stock conditions as indicated by the results of the PER, DDM and DCF valuation methods, a comparative analysis was carried out with the RMSE to see which stock valuation method was the most accurate. It is shown that DDM has the smallest deviation value so that DDM is the most accurate stock valuation method in stock fundamental analysis.